Assessment of knowledge, practices and barriers to foot care among patients with diabetes mellitus at Zomba Central Hospital, Malawi - Chibwe, Evelyn (2021)
Foot ulceration is one of the most common complications among patients suffering from Diabetes Mellitus. Good knowledge and practice regarding foot care has been documented to reduce the risk of such foot complications and amputation. This descriptive cross sectional study was conducted to assess knowledge, assess practices and identify barriers to foot care among patients with diabetes at Zomba Central Hospital. A structured questionnaire was used to assess foot care knowledge, practices, and other related variables of 81systematically selected diabetic patients. Data obtained were analyzed using Statistical Package for the Social Sciences Software version 20.0. Descriptive statistics and bivariate correlations with 95% confidence interval were computed and findings have been presented in tables and figures. Of 81 Diabetes patients, 82.7% (n=62) had good knowledge and 26.6 % (n=21) had good practice on foot care. With regard to knowledge, 90.1% (n=73) were aware of the first thing to be done when they found redness/bleeding between their toes and 75.3% (n=61) were aware of the importance of inspecting the feet. Poor foot practices included; 81.5% (n=66) walked bare footed and 66.7% (n=54) used a stone to clean their feet. Barriers to foot care reported by respondents were: lack of knowledge and lack of money to buy appropriate materials. The findings have highlighted the gaps in knowledge, practices and barriers to foot care in DM patients. The study recommends enhancement of health education on foot care, continual motivation and support to patients with Diabetes. The study was done in one hospital, if multiple sites where used the data could have been enriched.